Identification of Ecological Priority Areas Based on Nested-Scale Analysis: A Case Study of Metropolitan Nanjing, China - Yuxi Zhu; Jianqiang Yang; Le Zhu; Liping Sun (Land)
Rapid urbanization has led to severe fragmentation of ecological spaces in high-density metropolitan regions, threatening urban ecological security and environmental well-being. While cities explore various restoration strategies, the systematic identification of ecological priority areas remains an urgent challenge, particularly due to the limitations of multi-scale evaluation methods. This study develops an integrated nested-scale analytical approach to examine ecological elements at metropolitan and central urban levels, using Metropolitan Nanjing as a case study. The framework combines Morphological Spatial Pattern Analysis (MSPA), Landscape Connectivity Analysis, and INVEST Habitat Quality Assessment to identify ecological sources while employing a multi-dimensional ecological resistance evaluation system and Circuit Theory Model for critical node assessment. The findings reveal a notable spatial overlap between ecological pinch points and barrier points across scales, demonstrating the importance of nested-scale coupling in maintaining network stability. Through this analysis, 3297 ecological priority areas are identified and classified into three hierarchical categories, offering a practical framework for optimizing ecological networks in high-density metropolitan regions.